Implementasi Budaya Religius melalui Sistem Boarding School di Madrasah Aliyah Darus Shibyan Balung Kabupaten Jember - Ahmad Ihwanul Muttaqin; Imam Syafi’i (Journal of Islamic Education Research, 2021)
The school's religious culture is one of the ways the teacher instills religious values in students from the behavior carried out by the teacher towards the Islamic religion. The application of religious culture in the school environment aims to become a person who is aware of religion and has a noble character. The habituation of this religious culture can be achieved by implementing a boarding school system. To always fear God Almighty, have a noble character, and be moral. The research method used is a qualitative descriptive approach method. The qualitative descriptive approach method is basically in the form of data collected in the form of words, pictures, and not numbers. Everything that is collected is more or less the key to what has been researched. Data collection techniques use translating data sources consisting of observations, interviews, and documentation. The results of the research conducted can be concluded that a series of activities while at boarding school and the habits that are carried out can make good habits for students wherever they are. And can be applied when they return home. Through the religious culture that is applied, students always fear God Almighty, have a noble character, and are moral.